Evaluation of donor’s hormonal profile according to sex and age - de Assis Ramos, M. M.; Ricardo-da-Silva, F. Y.; Vidal-dos-Santos, M.; Vos, M. J.; Ottens, P. J.; Nieuwenhuijs-Moeke, G. J.; Correia, C. J.; Bakker, S. J. L.; Moreira, L. F. P.; Leuvenink, H.; Breithaupt-Faloppa, A. C.; , for TransplantLines investigators (Frontiers in Physiology, 2025)
Successful organ transplantation depends on several factors, including donor and recipient sex and age. Experimental data show that donor inflammatory status can be influenced by sex hormones, and, after brain death, there are significant differences in organ quality. Sex hormones also influence the immune system during different life stages, for example, during menopause there is a significant reduction in estrogen levels. Thus, the primary aim of this study is to evaluate the steroid profile of human donors after brain death. We performed a retrospective observational case-control study and selected samples from living (LD) and brain-dead (BD) donors from the TransplantLines Biobank and Cohort Study. Donors were stratified by age as Young (Y) from 20–40 years and Old (O), older than 55 years. Serum steroidal hormones from one hundred donors were analysed through LC-MS (Liquid Chromatography-Mass Spectrometry). In BD-females, cortisol and estradiol decreased significantly (p = 0.0001) in both age groups when compared to LD. However, an increase in progesterone was seen after BD for older donors (p = 0.0001). In BD-males, cortisol decreased significantly in both age (p = 0.0001) groups when compared to LD. For testosterone, the results were similar as BD decreased the steroid levels (p = 0.0001) compared to LD in both age groups. In conclusion, our results indicate that steroid hormone levels decrease after brain death.